An electrochemical impedance spectroscopy and scanning electron microscopy study of the influence of positive plate compression on the electrochemical behaviour of lead-acid batteries - De Marco, Roland; Lowe, Alexander; Sercombe, Matthew; Singh, P. (Pergamon-Elsevier Science Ltd, 2006)
This study has developed an electrochemical impedance spectroscopy (EIS) method for the in situ investigation of the influence of positive plate compression on the electrochemical behaviour of lead-acid batteries during charge/discharge cycling. The EIS data for a fully charged and fully discharged battery are internally consistent with the expected kinetics of a battery in the opposite states of charge, and demonstrate that EIS measurements may be recorded with a high level of reproducibility. Furthermore, this study has necessitated the development of a special cell incorporating horizontally orientated battery plates that can be subjected to elevated pressure through the stacking of lead bricks on top of the cell, as well as a physically robust reference electrode system that can withstand the application of pressure. For this purpose, a platinum-wire pseudo-reference electrode has been developed, and has been shown to exhibit sufficient electrode stability over the period of an EIS recording, enabling the measurement of reproducible and meaningful EIS data. Additionally, the influence of positive plate compression on the behaviour of the lead-acid battery has been investigated by using scanning electron microscopy (SEM). Clearly, the experimental data show that plate compression enhances significantly the kinetics and concomitant performance of the lead-acid battery, and this is related to the enhanced reactivity of the active material, as rationalized by using the agglomeration-of-spheres (AOS) model.